PECULIARITIES OF FORMATION OF CIVIL ENGAGEMENT OF UNIVERSITY STUDENTS IN QUARANTINE CONDITIONS - Shykyrynska, Oleksandra; Vyshkivska, Vanda; Petliaieva, Vera; Voichun, Olena; Malinka, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article defines the essence of the concept of “civic engagement of university students” and the process of formation of civic engagement of university students in quarantine conditions. The structure of civic engagement of university students is characterized. Criteria are substantiated and indicators of the formation of civic engagement of university students are defined: incentive criterion (sustainable social motives for achieving socially significant goals, the student’s achievement motive, value attitude to future professional activities); epistemological criterion (knowledge about public organizations and their activities, awareness of knowledge of civic responsibility, the presence of civic consciousness) behavioral (leadership ability, responsibility for own decisions, actions and team actions) creatively developing criterion (the presence of self-knowledge skills, the ability to introspection , self-esteem, self-criticism of the results of one's own socially useful activity). The substantive characteristic of such levels of formation of civic engagement of university students as: insufficient, initial, sufficient, high is given. The use of such digital tools is shown, which allows to form effectively the civic engagement of university students in quarantine conditions: a) the creation of an author's blog (to display information about: the national identity of the Ukrainian people (history, traditions, language, culture, etc.), planned for the future and already organized events by the student self-government were held, video and photo reports of the events) b) use of Google applications (Google meet - for conferences, meetings, online consultations; Google Drive, Google forms - for online questionnaires with the aim of : predicting the relevance of the event, it is planned, determining the effectiveness of the activities, identifying the psychological atmosphere in the team, identifying the socio-psychological characteristics of students, student awareness; Google photos; Google calendar; Google video). The results of an experimental study on the formation of civic engagement of university students, carried out during 2019 at V.O. Sukhomlynskyi Mykolaiv National University, are presented, which proves the practical importance of using such digital tools in quarantine conditions.